Reactive kinetics of carbon dioxide loaded aqueous blend of 2-amino-2-ethyl-1,3-propanediol and piperazine using a pressure drop method - Ullah, S. (2019)
In this study, a new pressure drop method has been used to investigate the kinetics of carbon dioxide reaction with aqueous blend of 2-amino-2-ethyl-1,3-propanediol (AEPD) with piperazine (PZ). The blending of a small amount of PZ with AEPD has a significant effect on the observed rate constant, kobs. It was observed that kobs values of the blend increased more than twice than the summation of kobs values of individual alkanolamines. The reaction kinetics in this study were modeled by assuming a termolecular mechanism. The addition of 0.1Â mol/L of PZ to 1Â mol/L AEPD exhibited an observed rate constant, kobs of 8824.1Â sâ1, which is comparable to other alkanolamine mixtures. Hence, PZ/AEPD mixtures can be potentially used for rapid carbon dioxide capture. Â© 2019 Wiley Periodicals, Inc.